The Accuracy of Prehospital Fluid Resuscitation of Burn Patients: A Systematic Review - Fahad Alsaqabi; Zubair Ahmed (MDPI AG, 2022)
Early management of burns is an essential component of achieving desirable patient outcomes. One of the earliest points of patient management in the case of burn injuries is in the prehospital setting. Unlike first aid, which can be provided by a non-healthcare worker, fluid resuscitation can be provided in the prehospital setting by emergency medical services personnel. This systematic review aims to investigate whether burn patients are receiving accurate fluid resuscitation in the prehospital setting. In addition, it will investigate if existing inaccuracies could impact patient outcomes negatively. This systematic review was completed in accordance with the guidelines from the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The search for eligible studies started by searching relevant databases (PubMed, Embase, Medline, and Google Scholar). The selected studies were screened, and data were extracted and analyzed using a narrative synthesis approach. Seven studies met the inclusion criteria of this review, with a total of 961 patients. All seven studies included in this review reported that the volume of fluids for resuscitation purposes received by burn patients in the prehospital setting was inaccurate. However, most reported that the patient outcomes were not affected. Most of the studies were rated as "good," however, and further high-quality randomized control studies are required before strong recommendations can be made.